Adalimumab for maintenance treatment of Crohn's disease: results of the CLASSIC II trial. Issue 9 (13th February 2007) - Sandborn, W J; Hanauer, S B; Rutgeerts, P; Fedorak, R N; Lukas, M; MacIntosh, D G; Panaccione, R; Wolf, D; Kent, J D; Bittle, B; Li, J; Pollack, P F
Abstract : Background: Adalimumab induced clinical remission after four weeks in patients with active Crohn's disease in the CLASSIC I trial. Objective: To evaluate long term efficacy and safety of adalimumab maintenance therapy in Crohn's disease in a follow-on randomised controlled trial (CLASSIC II). Methods: In the preceding CLASSIC I trial, 299 patients with moderate to severe Crohn's disease naive to tumour necrosis factor antagonists received induction therapy with adalimumab 40 mg/20 mg, 80 mg/40 mg, or 160 mg/80 mg, or placebo, at weeks 0 and 2. In all, 276 patients from CLASSIC I enrolled in CLASSIC II and received open-label adalimumab 40 mg at weeks 0 (week 4 of CLASSIC I) and 2; 55 patients in remission at both weeks 0 and 4 were re-randomised to adalimumab 40 mg every other week, 40 mg weekly, or placebo for 56 weeks. Patients not in remission at both weeks 0 and 4 were enrolled in an open-label arm and received adalimumab 40 mg every other week. With non-response or flare, these patients could have their dosages increased to 40 mg weekly. Patients in the randomised arm with continued non-response or disease flare could switch to open-label adalimumab 40 mg every other week and again to 40 mg weekly. The primary end point was maintenance of remission (CDAI <150) in randomised patients through week 56. Results: Of 55 patients randomised at week 4, 79% who received adalimumab 40 mg every other week and 83% who received 40 mg weekly were in remission at week 56, v 44% for placebo (p<0.05). In all, 204 patients entered the open-label arm. Of these, 93 (46%) were in clinical remission at week 56. Adalimumab was generally well-tolerated in all patients. Conclusions: Adalimumab induced and maintained clinical remission for up to 56 weeks in patients with moderate to severe Crohn's disease naive to anti-TNF treatment.